1990
DOI: 10.1136/bmj.301.6757.907
|View full text |Cite
|
Sign up to set email alerts
|

Six years' audit of laboratory workload and rates of referral for colposcopy in a cervical screening programme in three districts.

Abstract: Objective-To determine laboratory workload and rates of referral for colposcopy in a three district cervical screening programme during 1983-9 to assess the feasibility of accommodating call up of all women at risk, recall at three year intervals (now five year intervals), and investigation of women with all degrees of abnormality.Design-Analysis of computerised screening histories dating back to 1977 of women screened in the Avon cervical screening programme.Setting-Three district health authorities covering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…We found that a substantial proportion of the smears (about 25%) were from the follow-up of at least one cytological or histological diagnosis. Similar observations have been presented elsewhere with a proportion of follow-up smears between 12% and 30% (19). This systematic investigation and follow-up of positive, suspicious or atypical smears may be a possible explanation for the C Actcl Ohurt Ginetol Scand 73 (1994) 80.4%.…”
Section: Resultssupporting
confidence: 86%
“…We found that a substantial proportion of the smears (about 25%) were from the follow-up of at least one cytological or histological diagnosis. Similar observations have been presented elsewhere with a proportion of follow-up smears between 12% and 30% (19). This systematic investigation and follow-up of positive, suspicious or atypical smears may be a possible explanation for the C Actcl Ohurt Ginetol Scand 73 (1994) 80.4%.…”
Section: Resultssupporting
confidence: 86%
“…The baseline assumption of the authors was that the prevalence of high-risk HPV infections in histologically normal women is the same in both developed and developing countries 41 . Even a prevalence twice as high in developing countries would not significantly affect the results, except for increasing the number of colposcopies, a frequent source of workload increase in many of the screening programmes 44 . Not unexpectedly, if cervical cancer is supposed to develop only in the presence of high-risk HPV types, the advantages of HPV testing compared with conventional cytology would be accentuated.…”
Section: Hpv Testing As a Screening Tool For Cervical Cancer In The Dmentioning
confidence: 99%
“…Avon dealt with it in 1987, described its approach in the BMJ in 1991,8 and has been cited as an example of good practice 9. During 15 years with a strict five year interval, returning non-indicated tests to the sender, we receive perhaps three queries a year from women, their partners, their members of parliament, or the press.…”
mentioning
confidence: 99%